Dynamic Neuroimaging Biomarkers of Smoking in Young Smokers - Xue, Ting; Dong, Fang; Huang, Ruoyan; Tao, Zhanlong; Tang, Jun; Cheng, Yongxin; Zhou, Mi; Hu, Yiting; Li, Xiaojian; Yu, Dahua; Ju, Haitao; Yuan, Kai (Frontiers in Psychiatry, 2020)
Objective: To examine potential changes in the dynamic characteristics of regional neural activity in young smokers and to detect whether the changes were associated with smoking behavior. Methods: The dynamic regional homogeneity (dReHo) and dynamic amplitude of low-frequency fluctuations (dALFF) in 40 young smokers and 42 nonsmokers were compared. Correlation analyses were also performed between dReHo and dALFF in areas showing group differences and smoking behavior (e.g., the Fagerström Test for Nicotine dependence (FTND) scores and pack-years). Results: Significantly differences in dReHo variability were observed in the inferior frontal gyrus (IFG), superior frontal gyrus (SFG), medial frontal gyrus (MFG), insula, cuneus, postcentral gyrus, inferior semi-lunar lobule, orbitofrontal gyrus and inferior temporal gyrus (ITG). Young smokers also showed significantly increased dALFF variability in the anterior cingulate cortex (ACC) and ITG. Furthermore, a significant positive correlation was found between dALFF variability in the ACC and the pack-years; whereas a significant negative correlation between dReHo variability in the IFG and the FTND scores was found in young smokers. Conclusion: The pattern of resting state regional neural activity variability was different between young smokers and nonsmokers. Dynamic regional indexes might be a novel neuroimaging biomarker of smoking behavior in young smokers.